Fashion for God: religious textiles from hidden churches in the Dutch Republic 1580-1800 - Arts, Pim (Waanders Publishers, 2023)
"Traditionally, priest's vestments have been pre-eminently the objects on which the most attention and money was spent in a church. They were, and often still are, of a dazzling and heavenly beauty. When the survival of the Catholic Church was threatened during the Republic and Catholic shelter churches were not allowed to be recognisable from the street, what was not allowed to be shown on the outside was compensated for on the inside. In the 17th century, the robes became gold, silver and silk expressions of silent resistance, but also of a feminist agenda of the makers. Behind closed doors, everything was literally and figuratively pulled out to propagate the Catholic faith. Worn ball gowns with colourful flowered French, English and Chinese fashion fabrics were donated to the church by rich, pious women so that beautiful and special church vestments could be made from them. So it could easily happen that a priest in a pink robe with flowers stood at the altar"--